Context-dependent information space for construction information processes. (August 2019) - Hilbert, F; Schülbe, R; Fuchs, S
Abstract: The planning and construction of buildings and structures is based on collaborative building information processes. The information supply of these processes is characterized by the exchange of heterogeneous domain-specific information. For the treatment of most problems in the construction industry, the information involved is rarely considered in isolation, but rather elements from different information models are linked with each other. The concept of the information space has established itself for the persistence of such linked information models. For sustainable building, the continuous use of existing information models or information spaces is indispensable. Various implementation approaches exist for information spaces in civil engineering. One approach that is currently in the initial phase of standardisation and will therefore spread further in the construction industry is the multimodel approach. For large construction projects or more complex buildings, multimodels become very large and often contain information that is unnecessary for the respective processing situation. This makes the handling of such multimodels cumbersome and slows down the acceptance. One approach to reducing multimodels is to adapt them to the information needs of the respective information process. Information processes are embedded in a task context that essentially determines the information requirements of the process. In order to anticipate such situational information needs, this paper presents a method to define context-adaptive multimodel templates based on a formalization of the context dependencies of the information requirements. These can be evaluated at the time of application towards situation-specific information requirements and form a basis for the creation of situational information spaces for the realization of a context-oriented information supply.